Ionized gas discs in elliptical and S0 galaxies at z < 1 - Jaffe, Yara L.; Aragón-Salamanca, Alfonso; Ziegler, Bodo; Kuntschner, Harald; Zaritsky, Dennis; Rudnick, Gregory; Poggianti, Bianca M.; Hoyos, Carlos; Halliday, Claire; Demarco, Ricardo (Oxford University Press, 2014)
We analyse the extended, ionized-gas emission of 24 early-type galaxies (ETGs) at 0 < z < 1 from the ESO Distant Cluster Survey (EDisCS). We discuss different possible sources of ionization and favour star formation as the main cause of the observed emission. 10 galaxies have disturbed gas kinematics, while 14 have rotating gas discs. In addition, 15 galaxies are in the field, while 9 are in the infall regions of clusters. This implies that, if the gas has an internal origin, this is likely stripped as the galaxies get closer to the cluster centre. If the gas instead comes from an external source, then our results suggest that this is more likely acquired outside the cluster environment, where galaxy–galaxy interactions more commonly take place. We analyse the Tully–Fisher relation of the ETGs with gas discs, and compare them to EDisCS spirals. Taking a matched range of redshifts, MB < −20, and excluding galaxies with large velocity uncertainties, we find that, at fixed rotational velocity, ETGs are 1.7 mag fainter in MB than spirals. At fixed stellar mass, we also find that ETGs have systematically lower specific star formation rates than spirals. This study constitutes an important step forward towards the understanding of the evolution of the complex ISM in ETGs by significantly extending the look-back-time baseline explored so far.